PENGARUH KUALITAS LAYANAN DAN KEPUASAN EMOSIONAL TERHADAP KUALITAS HUBUNGAN DAN LOYALITAS PELANGGAN KFC DI SURABAYA - Tiya Gita Pawitra; Soni Harsono (Journal of Business & Banking, 2013)
Some factors are deemed to be important for research in relation to customer loyalty. These factors are service quality, emotional satisfaction, relationship quality. The purpose of this study is to analyze the influence of service quality, emotional satisfaction, relationship quality on customer loyalty Kentucky Fried Chicken (KFC) in Surabaya. The sample taken consists of KFC Jalan Ahmad Yani Surabaya customers. Analysis tool used is the Structural Equation Modeling (SEM). The results showed that there is a significant and positive effect of service quality of emotional satisfaction, emotional satisfaction a positive significant effect on customer loyalty. Beside, emotional satisfaction has positive and significant effect on the quality of relationships.